From EFL classroom language to classroom lexicon: Importing formulaic story language into teacher talk - MASONI, LICIA (Glottodidactica, 2019)
This paper reports on a language activity carried out in an Italian University with student teachers attending a primary education course. The activity was designed to train them to use authentic children’s picturebooks as a source for EFL language learning. It consisted of identifying and ‘noticing’ (Mackey 2006) multiword expressions and ready-made utterances in a number of authentic picturebooks and simulating instances of weaving the picturebook language into the fabric of daily classroom talk. Following the activity, the students wrote individual pieces of reflective writing describing their experience. Comments by student teachers assessed the use of picturebook-derived formulaic language on both their learning and perceived ability to teach English, and revealed much about their pedagogical perspectives on teacher talk. Results suggest that promoting the use of authentic and meaningful language in context can help student teachers conceive of classroom communication as lexicon (a shared communicative practice the rules of which are fully known only by a restricted community of speakers) rather than mere language-based interaction.